Geogenic arsenic and Microbial contamination in drinking water sources: Exposure risks to the coastal population in Bangladesh - Saha, Ratnajit; Dey, Nepal C.; Rahman, Mahfuzar; Bhattacharya, Prosun; Rabbani, Golam H. (Frontiers, 2022)
This article was published in the Frontiers in Environmental Science [© 2019 Saha, Dey, Rahman, Bhattacharya and Rabbani. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY).] and the definite version is available at: https://doi.org/10.3389/fenvs.2019.00057 The Journal's website is at: https://www.frontiersin.org/articles/10.3389/fenvs.2019.00057/full#h1